Reporting Practices and Resource Utilization in the Era of Intraductal Carcinoma of the Prostate: A Survey of Genitourinary Subspecialists. (May 2020) - Gandhi, Jatin S.; Smith, Steven C.; Paner, Gladell P.; McKenney, Jesse K.; Sekhri, Radhika; Osunkoya, Adeboye O.; Baras, Alexander S.; DeMarzo, Angelo M.; Cheville, John C.; Jimenez, Rafael E.; Trpkov, Kiril; Colecchia, Maurizio; et al.
Abstract : Intraductal carcinoma of the prostate (IDC-P) has been recently recognized by the World Health Organization classification of prostatic tumors as a distinct entity, most often occurring concurrently with invasive prostatic adenocarcinoma (PCa). Whether documented admixed with PCa or in its rare pure form, numerous studies associate this entity with clinical aggressiveness. Despite increasing clinical experience and requirement of IDC-P documentation in protocols for synoptic reporting, the specifics of its potential contribution to assessment of grade group (GG) and cancer quantitation of PCa in both needle biopsies (NBx) and radical prostatectomy (RP) specimens remain unclear. Moreover, there are no standard guidelines for incorporating basal cell marker immunohistochemistry (IHC) in the diagnosis of IDC-P, either alone or as part of a cocktail with AMACR/racemase. An online survey containing 26 questions regarding diagnosis, reporting practices, and IHC resource utilization, focusing on IDC-P, was undertaken by 42 genitourinary subspecialists from 9 countries. The degree of agreement or disagreement regarding approaches to individual questions was classified as significant majority (>75%), majority (51% to 75%), minority (26% to 50%) and significant minority (⩽25%). IDC-P with or without invasive cancer is considered a contraindication for active surveillance by the significant majority (95%) of respondents, although a majority (66%) also agreed that the clinical significance/behavior of IDC-P on NBx or RP with PCa required further study. The majority do not upgrade PCa based on comedonecrosis seen only in the intraductal component in NBx (62%) or RP (69%) specimens. Similarly, recognizable IDC-P with GG1 PCa was not a factor in upgrading in NBx (78%) or RP (71%) specimens. The majority (60%) of respondents include readily recognizable IDC-P in assessment of linear extent of PCa at NBx. A significant majority (78%) would use IHC to confirm or exclude intraductal carcinoma if other biopsies showed no PCa, while 60% would use it to confirm IDC-P with invasive PCa in NBx if it would change the overall GG assignment. Nearly half (48%, a minority) would use IHC to confirm IDC-P for accurate Gleason pattern 4 quantitation. A majority (57%) report the percentage of IDC-P when present, in RP specimens. When obvious Gleason pattern 4 or 5 PCa is present in RP or NBx, IHC is rarely to almost never used to confirm the presence of IDC-P by the significant majority (88% and 90%, respectively). Most genitourinary pathologists consider IDC-P to be an adverse prognostic feature independent of the PCa grade, although recommendations for standardization are needed to guide reporting of IDC-P vis a vis tumor quantitation and final GG assessment. The use of IHC varies widely and is performed for a multitude of indications, although it is used most frequently in scenarios where confirmation of IDC-P would impact the GG assigned. Further study and best practices recommendations are needed to provide guidance with regards to the most appropriate indications for IHC use in scenarios regarding IDC-P. Abstract : Supplemental Digital Content is available in the text.